Human Resource Management: Concept & Significance - Gadadh Latha (AG Volumes, 2021)
Human resource manager plays an essential role within industrial organisations’ ability to compete, and this study identifies the role it plays by examining the recruitment, training, motivation, attraction, hiring, and evaluation of employees, as well as the setting of wages, fees, including rewards. The development of HRM from the beginning of time will be addressed in such a theoretical framework in this study. The strategic importance of human resources within 21st-century enterprises will next be examined, as will the advancements in HRM in this century. Two industrial businesses in the city of Amman were used as an example for this study. Employee training, motivation, recruitment, hiring, and evaluation, as well as the determination of employee fees as well as rewards, were found to have a significant impact on industrial business organisations’ ability to compete. Furthermore, this finding is in line with that of earlier research.